EVALUASI PERTUMBUHAN TANAMAN MAHONI (Swietenia macrophylla King) PADA AREAL BEKAS STOCKPILE PT. JORONG BARUTAMA GRESTON ( JBG ) KALIMANTAN SELATAN - Hikmatul Ula; Eny Dwi Pujawati; Damaris Payung (Universitas Lambung Mangkurat, 2020)
The aims of this study to determine the effect of liquid fertilizer Lobo, Polyfert, Bionature on the growth of Mahogany plants and this research is the benefits to provide the best information of fertilizer that can be used in the maintenance of Mahogany plants. The design used in this study is Completely Randomized Design (RAL) with 4 treatments and repetition as much as 40 times, so the number of plants observed as many as 160 plants. The parameters calculated in this study were the increase of plant height of each treatment, the increase of leaf number per treatment and the diameter of the stem per treatment. The results of variance analysis on plant height increase data showed that the fertilizer treatment was not significant, but the highest value was obtained on Polyfert fertilizer and thelowest was on the control treatment. The result of varian analysis to data of plant diameter increase showed that the fertilizer treatment was very significant, but the highest value was obtained on Polyfert fertilizer and the lowest was on Bionature fertilizer. While the result of varian analysis to data of increase of leaf number of plants, showed that the fertilizer treatment was very significant, but the highest value was obtained on Polyfert fertilizer and the lowest was on the control treatment.Keywords: Mahogany; Plants ; Polyfer Fertilizer; Lobo Fertilizer; Bionature Fertilizer.